Impact of CYP2D6 activity and cachexia progression on enantiomeric alteration of plasma tramadol and its demethylated metabolites and their relationships with central nervous system symptoms in head and neck cancer patients. Issue 3 (20th November 2020) - Suzuki, Koji; Naito, Takafumi; Tanaka, Hironari; Shibata, Kaito; Yamada, Yasuhide; Itoh, Kunihiko; Kawakami, Junichi
Abstract: This study aimed to evaluate the influence of CYP2D6 activity and cachexia progression on the enantiomeric alteration of plasma tramadol and its demethylated metabolites in head and neck cancer patients. Fifty‐three head and neck cancer patients receiving oral tramadol were enrolled. The plasma concentrations of tramadol, O ‐desmethyltramadol (ODT) and N ‐desmethyltramadol (NDT) enantiomers were determined. The CYP2D6 activity score (AS) and degree of cachexia progression were assessed according to genotype and the Glasgow Prognostic Score (GPS), respectively. The enantiomeric ratio of NDT was (+)‐form dominant in all patients. CYP2D6 AS had negative correlations with the plasma concentrations of (+)‐NDT and (−)‐NDT. The plasma concentrations of (+)‐tramadol and (+)‐ODT were higher in patients with GPS 1 or 2 than in those with GPS 0. Lower metabolic ratios to NDT enantiomers were observed in patients with GPS 1 or 2. In patients with GPS 1 or 2, the plasma (−)‐tramadol was associated with the incidence of central nervous system symptoms. In conclusion, CYP2D6 AS partially explained the contribution of CYP2D6 activity to plasma tramadol and its demethylated metabolite enantiomers. Additionally, cachexia progression elevated the plasma (+)‐tramadol and (+)‐ODT levels through the reduction of N ‐demethylation of (+)‐tramadol.